2020
DOI: 10.1186/s40168-020-00811-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictable modulation of cancer treatment outcomes by the gut microbiota

Abstract: The gut microbiota has the potential to influence the efficacy of cancer therapy. Here, we investigated the contribution of the intestinal microbiome on treatment outcomes in a heterogeneous cohort that included multiple cancer types to identify microbes with a global impact on immune response. Human gut metagenomic analysis revealed that responder patients had significantly higher microbial diversity and different microbiota compositions compared to non-responders. A machine-learning model was developed and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 49 publications
5
94
0
Order By: Relevance
“…Data from a previous report has suggested that the treatment effects, including chemotherapy or a combination of chemotherapy with immunotherapy, in cancer patients are positively correlated with some speci c types of gut microbiota, such as Bacteroides ovatus and Bacteroides xylanisolvens [38]. However, the correlation between the e cacy of chemotherapy in lung cancer patients and certain speci c ora is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a previous report has suggested that the treatment effects, including chemotherapy or a combination of chemotherapy with immunotherapy, in cancer patients are positively correlated with some speci c types of gut microbiota, such as Bacteroides ovatus and Bacteroides xylanisolvens [38]. However, the correlation between the e cacy of chemotherapy in lung cancer patients and certain speci c ora is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Clostridium symbiosum and Ruminococcus gnavus were enriched in NR. 54 A second study analyzing fecal composition prior to preoperative concurrent chemoradiations in 45 rectal cancer patients concluded that Duodenibacillus massiliensis was linked to complete responses. 55 Altogether, the emerging field of oncoimmunomicrobiology is progressively integrating the gut microbiota into the parameters that determine the cancer immune set-point governing the clinical efficacy of immuno-chemo-radio-therapy.…”
Section: Gut Oncomicrobiota Signatures Associated With Response To Icismentioning
confidence: 99%
“…It seems, therefore, possible that taking into consideration the status of their microbiome may improve the use of antimicrobial agents, as well as the treatment outcomes for cancer patients [156]. Protocols for microbiota modulation may provide tools to achieve predictive information on cancer treatment outcomes [157][158][159].…”
Section: Central Regulatory Role Of the Microbiotamentioning
confidence: 99%